Influence of Corporate Image and ExperienceEmployee Job Satisfaction and Employee Performance at PT PLN (Persero) UP3 Palopo , Indonesia: - Nurlela Nurlela; Haedar Haedar; Junaidi Junaidi (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to determine the effect of corporate image, employee experience, and job satisfaction on employee performance at PT PLN (Persero) UP3 Palopo. Methodology: Using a quantitative associative approach, 52 respondents were selected from 119 employees through simple random sampling. Data analysis used multiple linear regression after validity and reliability testing. Results: The results showed that employee experience and job satisfaction had a positive and significant effect on employee performance, while corporate image had no significant effect on employee performance. Simultaneously, the three variables had a significant effect on employee performance, with a coefficient of determination (R) of 0.628. Findings: These results indicate that improving work performance and job satisfaction can substantially increase employee productivity and effectiveness. Novelty & Originality: The novelty of this study lies in its focus on the simultaneous examination of corporate image, employee experience, and job satisfaction within the context of a state-owned electricity company in a regional office setting (Palopo), which has been rarely explored in prior research. Its originality emerges from the empirical testing of these three variables in the Indonesian state-owned enterprise sector, particularly in the electricity utility industry. Conclusions: The study concludes that to enhance employee performance, PT PLN (Persero) UP3 Palopo should prioritize improving employee experience and job satisfaction through targeted human resource strategies, while recognizing that corporate image may not be a direct driver of performance in this specific context. Type of Paper: This paper is an empirical research paper.